Dynamics of digital entrepreneurship and the innovation ecosystem: A multilevel perspective. Issue 2 (15th October 2019) - Beliaeva, Tatiana; Ferasso, Marcos; Kraus, Sascha; Damke, Eloi Junior
Abstract : Purpose: The purpose of this paper is to investigate the dynamics of digital entrepreneurship and the role of innovation ecosystem in its shaping by applying a multilevel perspective on the phenomenon. Design/methodology/approach: An exploratory in-depth analysis of an IT company in Brazil is conducted using a quasi-mixed method design and three analytical techniques: pattern-matching, data exposure and social network analysis. The study is based on qualitative data, complemented by quantitative data. The case company is investigated within its time (historical development) and spatial (entire ecosystem) dimensions, providing an integrative approach to analysis. Findings: The results revealed significant differences in a set of supporting innovation ecosystem's actors and relationships throughout the development of the company from lower to higher levels of digitalization. The findings are discussed within a framework that links ecosystem's actors at different layers with different levels of business digitalization. Research limitations/implications: This research brings implications to SMEs in high-tech industries that are aiming to transform their business toward greater digitalization, and stresses the importance of strategic partners in innovation ecosystem in this process. Originality/value: The novelty of this research is related to how external actors contribute to a company to adapt and create value, and how companies may exploit opportunities by configuring internal resources and external assets from strategic relationships. The study considers digital entrepreneurship in dynamics, distinguishes between different levels of digitalization and prescribes them different enablers and sets of relationships.